2012
DOI: 10.1111/1471-0528.12055
|View full text |Cite|
|
Sign up to set email alerts
|

The determinants of minimal levator hiatus and their relationship to the puborectalis muscle and the levator plate

Abstract: Objective To determine the muscles comprising the minimal levator hiatus.Design Cross-sectional study.Setting The University of Oklahoma Health Sciences Center, USA.Population Eight female fresh frozen pelves and 80 nulliparous women.Methods Three-dimensional endovaginal ultrasound was performed in eight fresh frozen female pelves. The structures of the levator hiatus were tagged with needles and the cadavers were dissected to identify the tagged structures. A group of 80 nullipara underwent 3D endovaginal ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 24 publications
(52 reference statements)
3
43
0
Order By: Relevance
“…It is known that there is a moderate correlation between ultrasound detected LAD and pelvic organ prolapse . Normal ranges of MLH area, LPDA and ARA measurements with EVUS in normal nulliparous women has been reported previously . Mean of MLH area, LPDA, and ARA in normal nulliparous women were 13.6 cm 2 , 15.9°, and 156.8°, respectively.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It is known that there is a moderate correlation between ultrasound detected LAD and pelvic organ prolapse . Normal ranges of MLH area, LPDA and ARA measurements with EVUS in normal nulliparous women has been reported previously . Mean of MLH area, LPDA, and ARA in normal nulliparous women were 13.6 cm 2 , 15.9°, and 156.8°, respectively.…”
Section: Discussionsupporting
confidence: 57%
“…It has been shown that lack of adequate pelvic organ support is associated with changes in static and dynamic shape of pelvic floor . The detailed anatomy of the levator plate as it relates to the levator ani muscle subdivisions has been reported . Furthermore, using EVUS the LAD score's relationship to pelvic organ prolapse severity has been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that images obtained using EVUS have good-to-very good correlation in cadaveric sections for pelvic floor muscle subdivisions. 10,39 Post-processing of the images acquired on 3D-EVUS facilitates the evaluation of LAM in the plane of minimal hiatal dimensions, and good-to-excellent correlation has been reported in the LH measurements. 8 A recent publication has studied the change in LH dimensions using 3D high-frequency EVUS 1 year before and after treatment for POP and found that in contrast to conservative management, there is a significant decrease in LH dimensions 12 months following surgery.…”
Section: Techniquementioning
confidence: 99%
“…These two major components of the 'continence control system' function separately [25] and may compensate one another to maintain continence [10,26]. Normal urethral support system requires the contraction of the levator ani muscle which supports the urethra through elevation of the pubocervical fascia [27]. During a cough, there is simultaneous contraction of the levator ani muscle, the diaphragm and abdominal wall muscles to build abdominal pressure.…”
Section: Discussionmentioning
confidence: 99%